Double-Edged Sword Effect of High-Performance Work System on Employee Well-Being—Moderating Effect of Union Practice - Qi, Wei; Enhua, Hu; Jiandong, Sun; Hongmei, Shan (Frontiers in Psychology, 2021)
Improving employees' well-being is the inevitable choice to improve corporate performance and competitive advantage and the social responsibility that enterprises must undertake. Based on the job demands-resources model, this paper introduces perceived organizational support and work stress as the mediator and trade union practice as the moderator to explore the double-edged sword effect of high-performance work systems on employee well-being. Taking 243 employees from China as samples, we found that high-performance work systems positively affect employee well-being through perceived organizational support and negatively affect employee well-being through work pressure. Union practices can significantly reduce the positive effect of high-performance work systems on work pressure and further weaken high-performance work systems' negative effect on employee well-being through work stress. The results of this paper provide a new way to explain the impact of the high-performance work system on employees' well-being and find that union practice can weaken the negative effects of the high-performance work system. This paper provides a new thinking direction for improving the well-being of employees in enterprises.